Repurposing hydrochlorothiazide (HCTZ) for colorectal cancer: a retrospective and single center study - Foo, Dominic Chi-Chung; Li, Jiaxi; Huang, Zheng; Sui, Siming; Sin, Ryan Wai-Yan; Man, Abraham Tak Ka; Law, Wai-Lun; Ng, Lui (Frontiers in Pharmacology, 2025)
BackgroundAnti-hypertensive drugs have been reported to demonstrate anti-inflammatory and anti-angiogenic effects. This study aims to investigate the association between anti-hypertensive drugs and the prognosis of colorectal cancer (CRC) patients.MethodsClinical data of 1134 CRC patients with hypertensions and the prescription of anti-hypertensive drugs who had undergone curative surgery in our hospital between 2005 and 2015 were retrieved. Their survival data and immune cell population in circulatory blood were compared among different types of anti-hypertensive drugs and overall CRC patients.ResultsThe 5-year overall survival for the antihypertensives-treated patients (65.2%) was higher than the CRC patients in Hong Kong (58.2%). Hydrochlorothiazide (HCTZ) group showed the best prognosis (79.1%) among different antihypertensive drug, particularly for advance stage or elderly patients, which are poor prognostic factors for overall CRC patients, demonstrated an obviously improved prognosis upon HCTZ treatment. Moreover, our data showed the recurrence rate was significantly lower for HCTZ group (18.3%) compared to non-HCTZ group (26.8%) and the reported rate (31%) of CRC patients in Hong Kong. Finally, patients with a lower pre-operative basophil level showed better overall and disease-free survival following HCTZ treatment.ConclusionThis study demonstrated the association of HCTZ treatment with a better prognosis of CRC patients.